Estudos em sapindaceae - v. contribuição. ὰ sistemática de talisia olivaeformis (kunth) radlk (1983)
This paper presents taxonomic, ecological and palinological data on Talisia olivaeformis (Kunth) Radlk. - Sapindaceae - indicating the geographical distribution as well. The species studied is used as on ornamental plant for arborization and has edible fruits.